Transformasi Gender Dalam Kepemimpinan Perempuan Perspektif Hukum Islam - Irham, Muh.; Alamsyah, Muh Rizky; Ramli, Muh Alfaridzi; Kurniati, Kurniati (Jurnal Litigasi Amsir, 2024)
This study aims to explore the role of women in leadership in the modern era. Using library research methods, this study analyzes various literatures that discuss the differences in leadership styles between women and men and the challenges faced by women in leadership positions. The results of this study indicate that women have unique leadership characteristics, such as abilities that can support their leadership effectiveness. However, women still face various challenges, including gender stereotypes and discrimination. This study emphasizes the importance of awareness and support for women in taking leadership roles in various fields